Socio and Institutional Conditions of Farmers of the Private Forest in Tasikmalaya District - Dian Diniyati (Balai Litbang Teknologi Agroforestry, Ciamis, 2018)
Socio and institutional conditions may affect the private forest development in Tasikmalaya District. This research was conducted in Tanjungkerta, Sepatnunggal, and Karyabakti villages from March to July 2011. The aim of the research was to identify the socio and institution conditions of farmers. The numbers of respondents involved were 60 persons. Data were collected by implementing interview technique which was supported by questionnaires. The data consisted of the condition of social and the institution of farmers. The data were analyzed by using Dependency Ratio (DR), Labour Force Participation Rate (TPK), and Dependency Rate of the farmers toward forest business (RK). The result showed that the condition of social of farmers were characterized by age, sex, education, tribe, religion, marriage status, status in family, and family dependent. The values of DR and TPK toward private forest business were categorized as low, meanwhile the value of RK in Tanjungkerta, Sepatnunggal and Karyabakti Villages were 12.50 %, 16.42 % and 19.02 % respectively. The institutions available at research location were grouped into three groups i.e. 1) economic institution (cooperation and regular social gathering), 2) social institution (farmer group, farmer group union and recitation) and 3) mutual cooperation.